EFFECT OF MOLE DRAINAGE ON SOIL SALINITY AND OXIDATION REDUCTION POTENTIAL OF WATERLOGGED VERTISOLS IN ANDHRA PRADESH - A. SAMBAIAH*, M. RAGHU BABU, G. RAVI BABU, G.V. LAKSHMI; S.B.S. NARASIMHA RAO (The Journal of Research ANGRAU, 2020)
The effect of mole drainage at various spacings (2m, 3m, 4m and 5m) placed at different depths (0.4m b.g.l and 0.5m b.g.l) on salinity and oxidation reduction potential of the waterlogged vertisols in Kapileswarapuram village was studied from 2016-17 to 2017-18. It was found that the soil salinity (ECe (1:2.5) got reduced from 1.73 dS m-1 to 0.41dS m-1 and 0.58 dS m-1 in 0.4 m mole drain depth drains at 2m and 3m mole drain spacing, whereas, it got reduced to 0.46dSm-1and 0.62 dSm-1 in 0.5m mole drain depth drains with 2m and 3 m drain spacing respectively after 2 years of leaching and drainage. The positive net effect of mole drainage systems on improving ORP in sugarcane vertisols was significant as the recorded ORP was found to be 680mV, 603mV, 283mV and 166mV and -567 mV in 2m, 3m, 4m, 5m and check mole drainage spacing plots with 0.4m mole drain depth. Similarly, in 0.5m mole drain depth plots, the net effect of mole drainage systems on improving ORP in sugarcane vertisols was significant as the recorded ORP was found to be 567mV, 492mV, 242mV, 121mV and -532 mV in 2m, 3m, 4m, 5m and check mole drainage spacing plots. It was recorded that the response of vertisols oxidation reduction potential to mole drainage systems was found to be following the 2nd order polynomial relationship with the highest coefficient of determination.